Model Strategic Adaptive Management dalam Pengembangan Kurikulum Pondok Pesantren - Mustari, Mustari; Hakim, Muhammad Nur; Munir, Nur; Masrufa, Binti (At Tadbir: Islamic Education Management Journal, 2025)
This study aims to analyse the curriculum development strategy of the Nahdatul Ulum Sarampu Islamic boarding school in facing the challenges of globalisation and modernisation in education. In the context of today's competitive era, Islamic boarding schools are required to be adaptive and innovative in order to produce graduates who are not only excellent in religious studies but also competitive in the professional world. This study uses a qualitative approach with field research. Data was obtained through in-depth interviews with the Islamic boarding school leadership and the Head of the Education Bureau as the main sources, supported by observation and documentation. Data analysis was conducted inductively through the stages of data reduction, data presentation, and conclusion drawing based on the dynamics of the process in the field. The results of the study indicate that the curriculum development strategy at the Nahdatul Ulum Sarampu Islamic Boarding School is formulated based on the institution's vision and mission, taking into account community needs and global challenges. Curriculum planning is carried out systematically through in-depth studies by the pesantren leadership to determine the direction and objectives of the education programme. The strategy is implemented through the establishment of new educational units such as Tahfidzul Qur'an, Tartil Qur'an, and the Al-Miftah method, as well as the development of external activities that foster independence and skills among students in creating employment opportunities. The contribution of this research lies in emphasising the importance of integrating traditional pesantren values with the demands of educational modernisation, thereby producing a curriculum development model that is relevant, adaptive, and remains based on Islamic principles.